EFFECT OF TWO YEARS NATURAL AGING ON BURST PRESSURE OF OVER-PRESSURE COPPER TUBE (MT) - YANG Fan; LUO Feng; LIU Bing; ZHANG HongWei; FAN YouXiong; LIU XiaoNing (Jixie qiangdu)
To study the stability of the over-pressure reinforcement effect of the copper tube at room temperature, the burst tests for the small diameter soft TP2 copper tube at room temperature during the natural aging time of 0, 6, 12 and 24 months were carried out respectively. These results indicated that: the mean of the measured burst pressure did not change significantly for small diameter soft TP2 copper bare tube and rifled tube at the same pretreatment pressure during the natural aging time of 0, 6, 12 and 24 months, respectively. The standard deviation was gradually smaller and the over-pressure strengthening effect was obvious. The measured burst pressure was different obviously for small diameter soft TP2 copper tube at the pretreatment pressure was 4.60 MPa and 16.50 MPa respectively during the same natural aging time, the mean was significantly larger and standard deviation was significantly smaller for measured burst pressure with the increase of pretreatment pressure, the results showed that pretreatment pressure had a great influence on strengthening effect, and higher pretreatment pressure could get better strengthening effect. The burst pressure conforms to the normal distribution for the same small diameter soft TP2 copper tube at the same over-pressure reinforcement during the natural aging time shall not exceed 24 months. Over-pressure reinforcement at room temperature was a suitable method to increase burst pressure of soft TP2 copper tube, and the method could be used in engineering.